Speciation of VOC emissions related to offshore North Sea oil and gas production - Wilde, Shona E.; Dominutti, Pamela A.; Allen, Grant; Andrews, Stephen J.; Bateson, Prudence; Bauguitte, Stephane J.B.; Burton, Ralph R.; Colfescu, Ioana; France, James; Hopkins, James R.; Huang, Langwen; Jones, Anna E.; et al. (Atmospheric Chemistry and Physics, 2025)
Funding: Airborne data were obtained using the BAe-146-301 Atmospheric Research Aircraft (ARA) flown by Airtask Ltd. and managed by FAAM Airborne Laboratory, jointly operated by UK Research and Innovation (UKRI) and the University of Leeds, and a DCH6 Twin Otter operated by the British Antarctic Survey (BAS). The FAAM aircraft data were collected as part of the Demonstration Of A Comprehensive Approach To Monitoring Emissions From Oil and Gas Installations (AEOG) project, the Improved understanding of accidental releases from oil and gas industries offshore project, and the Methane Observations and Yearly Assessments (MOYA) project, all funded by the Natural Environment Research Council (NERC). The Twin Otter aircraft campaigns were funded under the Climate and Clean Air Coalition (CCAC) Oil and Gas Methane Science Studies (MSS), hosted by the United Nations Environment Programme. Funding was provided by the Environmental Defense Fund, Oil and Gas Climate Initiative, European Commission, and CCAC. We also acknowledge the Offshore Petroleum Regulator for Environment and Decommissioning (OPRED) and Ricardo Energy & Environment for their involvement as project partners on the AEOG project. The North Sea is Europe's key oil and gas (O&G) basin with the output currently meeting 3 %–4 % of global oil supply. Despite this, there are few observational constraints on the nature of atmospheric emissions from this region, with most information derived from bottom-up inventory estimates. This study reports on airborne measurements of volatile organic compounds (VOCs) emitted from O&G-producing regions in the North Sea. VOC source emission signatures for the primary extraction products from offshore fields (oil, gas, condensate, mixed) were determined in four geographic regions. Measured iso-pentane to n-pentane (iC5 / nC5) ratios were 0.89–1.24 for all regions, used as a confirmatory indicator of O&G activities. Light alkanes (ethane, propane, butane, pentane) were the dominant species emitted in all four ...